2016
DOI: 10.1186/s13033-016-0042-1
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the gap: investigating challenges and way forward for intersectoral provision of psychosocial rehabilitation in South Africa

Abstract: BackgroundIntersectoral collaboration between government sectors such as Health and Social Development and non-governmental organisations (NGOs) in communities is crucial for provision of psychosocial rehabilitation (PSR) for those with severe mental illness. This study aims to provide recommendations for strengthening such intersectoral collaboration in South Africa and with relevance to other low and middle income countries (LMIC), particularly African countries.MethodsTwenty-four in-depth semi-structured in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 40 publications
0
27
0
Order By: Relevance
“…The importance of intersectoral collaboration for suicide prevention, particularly in LMICs, has been described (Bertolote et al, 2006; Reynolds and Conroy, 1999; Wang et al, 2008; WHO, 2012). There are a number of obstacles to achieving intersectoral collaboration in LMICs (Brooke-Sumner et al, 2016). Intersectoral approaches to the treatment of mental illnesses in SA have not been adequately achieved, especially in rural areas, because of the lack of dedicated funding for such approaches (Petersen and Lund, 2011; Thornicroft et al, 2010), failures of management and leadership to implement relevant policy (Jenkins et al, 2011) and a lack of political will (Brooke-Sumner et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of intersectoral collaboration for suicide prevention, particularly in LMICs, has been described (Bertolote et al, 2006; Reynolds and Conroy, 1999; Wang et al, 2008; WHO, 2012). There are a number of obstacles to achieving intersectoral collaboration in LMICs (Brooke-Sumner et al, 2016). Intersectoral approaches to the treatment of mental illnesses in SA have not been adequately achieved, especially in rural areas, because of the lack of dedicated funding for such approaches (Petersen and Lund, 2011; Thornicroft et al, 2010), failures of management and leadership to implement relevant policy (Jenkins et al, 2011) and a lack of political will (Brooke-Sumner et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…A study focusing on South Africa showed some similar barriers and facilitators for ISC for health [39], wherein lack of communication between sectors was the main issue; each sector perceived a lack of support from the others [39]. Another barrier was that ISC is a life-long issue whereas the tenure of policy-makers is finite, posing a challenge of commitment and involvement [39]. Regionally, global policies and institutions still have too much influence on countries, sometimes overlooking country priorities, and as such hampering national ownership [40].…”
Section: Discussionmentioning
confidence: 99%
“…Such integrated approaches have been proposed in both the National Drug Master Plan 2013–2017 [ 68 ] and the National Mental Health Policy Framework and Strategic Plan 2013–2020 [ 33 ], although evidence for this integration is absent. Research has identified a lack of communication between sectors, problems delineating roles, and perceptions of not being supported by other sectors as some of the reasons for this lack of integration and intersectoral collaboration [ 69 ]. Suggestions for improving intersectoral collaboration have been recognised more generally for mental health in SA [ 69 ] but suggestions specific to suicide prevention are currently lacking.…”
Section: Discussionmentioning
confidence: 99%